2020
DOI: 10.1002/ece3.5940
|View full text |Cite
|
Sign up to set email alerts
|

Hollow oaks and beetle functional diversity: Significance of surroundings extends beyond taxonomy

Abstract: Veteran hollow oaks (Quercus spp.) are keystone structures hosting high insect diversity but are declining in numbers due to intensification of land use and the abandonment of traditional management. The loss of this vital habitat is resulting in a reduction of biodiversity, and this likely has consequences for ecosystem functioning, especially if functional diversity is reduced. A considerable amount of research has been done on predictors of beetle taxonomic diversity in veteran oaks, but predictors of funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 72 publications
2
19
0
Order By: Relevance
“…Although this study focused on the dichotomy between veteran and young trees at rather small spatial scales (200 m or less), other research has established that the immediate surroundings and the wider landscape around the veteran trees can influence invertebrate diversity 22 , 38 41 and that large scale anthropogenic factors such as urbanization gradients influence predation rates by natural enemies 12 , 26 . In contrast, research within agroecosystems has found that strips of non-agriculture area with resources for natural enemies reduce pests and crop plant damage independent of landscape complexity 42 .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Although this study focused on the dichotomy between veteran and young trees at rather small spatial scales (200 m or less), other research has established that the immediate surroundings and the wider landscape around the veteran trees can influence invertebrate diversity 22 , 38 41 and that large scale anthropogenic factors such as urbanization gradients influence predation rates by natural enemies 12 , 26 . In contrast, research within agroecosystems has found that strips of non-agriculture area with resources for natural enemies reduce pests and crop plant damage independent of landscape complexity 42 .…”
Section: Discussionmentioning
confidence: 98%
“…Habitat heterogeneity is important for predation by natural enemies, as it increases the possibility of multiple invertebrate enemies to coexist 11 , 12 and has been linked to a greater diversity of invertebrate predators 22 , 33 . The coexistence of natural enemies with complementary traits has been found to be the most important predictor of pest control by natural enemies 10 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations